Analysis of Technology Use in History Learning from a Social and Cultural Perspective in Senior High School in Pontianak City - Chalimi, Ika Rahmatika; Rudiyanto, Yustinus (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
This research aims to analyze the use of technology in history learning in high schools in Pontianak City from a social and cultural perspective. The research method uses a qualitative approach with a case study design to explore in depth the forms of technology used, teaching strategies, teacher and student perceptions, and obstacles encountered in the learning process. The findings demonstrate the widespread use of technologies like projectors, smartphones, design applications, and digital platforms in history education. Technology is considered capable of increasing student engagement, strengthening the visualization of materials, and creating more engaging learning. However, social challenges such as digital distractions, decreased direct interaction, and dependence on AI are beginning to appear in the learning process. From a cultural perspective, the dominance of global content and the limited availability of local digital resources pose obstacles to maintaining students' cultural identity. Teachers overcome these obstacles through critical digital literacy, local content curation, collaborative assignments, and the creation of media based on regional history. This study emphasizes the importance of using technology wisely and contextually to ensure that history learning remains aligned with socio-cultural values. The results of the research are recommended as a reference for developing school policies and teacher training to improve the quality of history learning in the digital era.